The Effectiveness of Endomycorrhiza Species on the Growth of Barangan Banana Seedlings - Asmah Indrawati; Suswati Suswati (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
Utilization of various species of arbuscular mycorrhizal fungi in Barangan banana nurseries has been carried out in a wire house. The aim of the study was to obtain data on the effectiveness of Barangan banana seedling growth after various FMA species were applied. This research was conducted with a Completely Randomized Design with mycorrhizal (A) treatment consisting of 4 levels, namely: A0. Without mycorrhizae, A1. Glomus type 1; A2. Acaulospora type 4 and A3. Glomus fasciculatum (FMA isolate collection of Prof. Dr. Ir. Eti Farda Husin, MS) with 5 replications. A total of 10 g of FMA inoculants were separately put into the acclimatization media of the Barangan plantlet in the form of a sterilized charcoal and sand mixture (2: 1). during acclimatization. The results of this study indicate that seedling growth is better in the treatment of FMA applications than in controls. Acaulospora type-4 FMA isolates; Glomus type-1 and G. fasciculatum can increase the height of Barangan banana seedlings at a rate of: 3.117%; 2,831% and 2,328% while the rate of leaf growth is better in Glomus type-1 applications (1,865%), G. fasciculatum (1,709%) and Acaulospora type 4 (1,412 and control (1,174%).